Redesigning the UI/UX of the Performance Monitoring Website at Pegadaian Regional Office XII Surabaya Using the Lean UX Method - Muhammad Ilyasa Mahardhika; Anindo Saka Fitri; Prasasti Karunia Farista Ananto (Universitas Islam Kuantan Singingi, 2025)
The performance monitoring website at Pegadaian Regional Office XII Surabaya played an important role in supporting evaluation activities; however, its suboptimal interface caused issues in usability, limited information access, and required manual coordination among staff. This study was conducted to redesign the user interface and user experience of the website in order to improve usability and user satisfaction. The research applied a practical approach using the Lean User Experience method, which emphasized iterative development through assumption formulation, prototyping, experimentation, and feedback analysis. The subjects of this study included staff from Business Analysis and Performance Evaluation, Distribution and Service Networks, as well as Marketing and Sales, who served as the primary users of the system. The initial design of the website received a System Usability Scale score of 43.5, which was categorized as unacceptable. After the redesign, the score significantly increased to 80, categorized as A-, indicating a very good level of usability. Furthermore, the results of the User Experience Questionnaire showed positive improvements in all dimensions, including attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. This study concluded that the redesign successfully enhanced usability and user experience, making the system more effective in supporting performance monitoring and decision-making within Pegadaian.